2003
DOI: 10.1080/0042098032000146876
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Call Centre Location: Some Evidence for UK Urban Areas

Abstract: This paper presents new evidence concerning the spatial distribution of UK call centre activity and analyses the determinants of this distribution. The study adopts a restructuring perspective, viewing call centre growth as a strategic response by companies seeking to develop competitive advantage and a process that is changing the spatial division of labour. The data indicate that there is an uneven spatial distribution of call centre activity in the UK. The results of econometric models, utilising Tobit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Research on UK peripheral regions confirms that call centres have until fairly recently provided a significant source of employment growth at least over the past ten years (BRISTOW, MUNDAY and GRIPAIOS 2000;BISHOP GRIPAIOS andBRISTOW 2003, DEPARTMENT OF TRADE AND INDUSTRY 2004). Despite the potential for locational dispersal throughout the urban hierarchy, however, studies have shown that call centres tend to be highly concentrated in larger urban centres.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Research on UK peripheral regions confirms that call centres have until fairly recently provided a significant source of employment growth at least over the past ten years (BRISTOW, MUNDAY and GRIPAIOS 2000;BISHOP GRIPAIOS andBRISTOW 2003, DEPARTMENT OF TRADE AND INDUSTRY 2004). Despite the potential for locational dispersal throughout the urban hierarchy, however, studies have shown that call centres tend to be highly concentrated in larger urban centres.…”
Section: Introductionmentioning
confidence: 89%
“…The data also confirms the concentration of these contact centres within the major conurbations of Greater Manchester, Merseyside and Central Lancashire where more than fourth fifths of these businesses are located. ContactBabel data also appears to show strong growth in employment in contact businesses during 2003-2004(PECK and CABRAS, 2005.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…In pursuit of low cost and abundant pools of labour, call centre work has become concentrated in many of the old industrial areas of the UK, superseding the previous layers of investment based upon branch plant manufacturing and heavy industries (Bishop et al, 2003;Richardson et al, 2000). Reflecting this broader trend, call centres have developed a strong concentration in Glasgow, spurred also by financial incentives and the availability of low-cost accommodation (Taylor and Anderson, 2012: 24).…”
Section: The Glasgow Local Lcr and Call Centresmentioning
confidence: 99%